1999
DOI: 10.1111/j.1600-0560.1999.tb01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and immunohistochemical studies of the periendothelial matrix in human melanoma: evidence for an amorphous matrix containing laminin

Abstract: Angiogenesis and the extracellular matrix are fundamental to tumor progression from in situ to invasive and metastatic disease. Laminin, a major glycoprotein integrated into basement membranes, is observed in angiogenesis and tumorigenesis. A recent study described an association between melanoma cells and endothelial cells via an amorphous matrix containing laminin. In the current study, we have examined 45 cases of human primary and metastatic melanomas by electron microscopy for the presence of an amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…8,9 The spread of tumor cells via EVMM was proposed based upon ultrastructural and immunohistochemical stains that demonstrated the close approximation of melanoma cells to blood vessel endothelial cells, in a pericytic location. [48][49][50] It has been shown that melanoma cells are separated from endothelial cells by an amorphous matrix containing 'free' laminin, which is not incorporated into the basement membrane, forming an 'angio-tumoral complex'. 48,49,51 The presence of the C16 laminin peptide increases the distance of angiotropic migration of melanoma cells in vitro.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The spread of tumor cells via EVMM was proposed based upon ultrastructural and immunohistochemical stains that demonstrated the close approximation of melanoma cells to blood vessel endothelial cells, in a pericytic location. [48][49][50] It has been shown that melanoma cells are separated from endothelial cells by an amorphous matrix containing 'free' laminin, which is not incorporated into the basement membrane, forming an 'angio-tumoral complex'. 48,49,51 The presence of the C16 laminin peptide increases the distance of angiotropic migration of melanoma cells in vitro.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
“…[48][49][50] It has been shown that melanoma cells are separated from endothelial cells by an amorphous matrix containing 'free' laminin, which is not incorporated into the basement membrane, forming an 'angio-tumoral complex'. 48,49,51 The presence of the C16 laminin peptide increases the distance of angiotropic migration of melanoma cells in vitro. 52 Furthermore, ex vivo and in vivo studies with time-lapse video microscopy have documented the migration of melanoma cells along the abluminal surface of vascular channels without blood vessel invasion, arguing against angiotropism just representing an early stage in the vascular invasion process.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
“…Although the surrounding tissue is typically matrix rich, the nests are almost entirely cellular with only small fragments of basement membrane proteins and fibronectin, and overall very low ECM compared with normal melanocytes or hyperplastic nevi (7,8). The high production of active proteases, both metalloproteinases and components of the plasmin system, probably contributes to the minimal ECM present within these tumors (9,10).…”
mentioning
confidence: 99%
“…Lugassy et al first described the pericyte-like position of invading melanoma cells along the blood vessel basal lamina [32][33][34] . In fact, 91% of cases of human melanoma reviewed in another study did not have a clearly defined basement membrane [35] . Building on these findings, human melanoma cells were shown to localize to both endothelial tubules formed in vitro as well as invade in a perivascular fashion when injected ex vivo into the brains of mice [6,36] .…”
Section: Pericyte Mimicry / Extravascular Migratory Metastasismentioning
confidence: 96%